The potential of biosensor as an early warning tool for disaster risk reduction at regional level - Ooi, Lia; Lee, Yook Heng; Goh, Choo Ta (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Recently, there is an increasing rate of environmental pollution cases reported, and that is closely related to technological hazard. Environmental monitoring (EM) is an approach to detect environmental risk before it develops into a disaster. Disaster Risk Reduction (DRR) is an important concept in reducing the impacts of hazards and disasters to social, economy and environment, especially at a regional level. Biosensors have been developed to detect pollutants and hazardous chemicals that are frequently and potentially found in the environment as a result of anthropogenic activity and as part of the natural phenomena. Efforts are focus in developing biosensors that are applicable in EM, some suggested biosensors could replace the conventional chemical analytical methods, but not all of them are practical. To evaluate the feasibility of biosensors in assisting EM in DRR, an analysis of articles published on biosensors in related field was carried out. Based on the evaluation, we concluded five major aspects to be considered when biosensors are to be applied as an early warning system tool in DRR at regional level, namely complexity of real sample, need of continuous environmental monitoring data, reproducibility of data, on-site testing and roles in risk characterization. This paper will help in the assessment of the applicability of biosensor in EM and as part in the DRR, and also as a guide to designing biosensor for EM purposes.